RANGKUL KELUARGA KENDALIKAN HIPERTENSI DENGAN MANAGEMENT DIIT - Kurniati Prihatin; Baiq Ruli Fatmawati; Aswati; Dewi Nur Sukma Purqoti; Zaenal Arifin; Alvin Abdillah (Stikes Yarsi Mataram, 2023)
Hypertension is a major risk factor for cardiovascular disease which can cause early morbidity or mortality. Hypertension therapy is long-term even for life and continuous care at home, so it is not only the involvement of the patient himself that is of concern but social support, especially the family, is also very important, especially in helping sufferers in carrying out therapy, both pharmacological and non-pharmacological therapy. The family plays an important role in modifying lifestyle and managing the type of diet for people with hypertension. This community service aims to provide diet counseling and education to families with hypertension so that they are able to help and support hypertension sufferers in diet management. This activity was attended by 30 family members of sufferers in Penimbung Timur Hamlet, Gunung Sari District, using LCD projectors and leaflets as media. The methods used are lectures, discussions and demonstrations regarding the use of kitchen spice measurements and giving examples of the right foods, fruits and vegetables.